Use of antibiotics in complex treatment of patients with secondary lymphostasis 1–2 degree - A. N. Shcherbyuk; V. M. Manuylov; Ya. E. Nemstsveridze; R. I. Stepanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
In lymphedema, various types of congenital and acquired anomalies of opened vessels and opened nodes are observed. They often lead to cardiac hypertension, valvular insufficiency, and lymphedema. Today, secondary lymphostasis ranks first among the pathologies of the cardiac system of the extremities. The etiology of this situation, which results in a mechanical disease of the current of the lymphatic system, is very different. However, the most common cause of secondary lymphostasis of the extremities is the blockade of inflammatory nodes and vessels after the inflammatory process in them [1].